The outcome of neurology outpatients with medically unexplained symptoms: a prospective cohort study. Issue 7 (1st July 2003) - Carson, A J; Best, S; Postma, K; Stone, J; Warlow, C; Sharpe, M
Abstract : Background: In a previous cross sectional study of 300 consecutive new attenders at neurology outpatient clinics, 90 were detected with symptoms that were rated as "not at all" or only "somewhat" explained by organic disease. Objective: To report a follow up study of this cohort. Methods: Patients were reinterviewed by telephone eight months after their initial assessment. They were asked to rate their overall improvement on a clinical global improvement scale, and their health status on the medical outcome short form 36 item scale (SF-36). The PRIME MD interview was administered to determine psychiatric diagnoses. Neurological and primary care records were reviewed for any changes in diagnostic opinion during the follow up period. Results: Of the 90 eligible patients, 66 (73%) participated in follow up. Among these, five (8%) rated themselves as "much worse, " four (6%) as "somewhat worse, " 27 (40%) as "just the same, " 15 (23%) as "somewhat better, " and 15 (23%) as "much better." There were no cases in which an organic cause for the presenting complaint was uncovered during the follow up period. Poorer physical function at baseline was the only predictor of poorer outcome at follow up. Conclusions: Over half the patients who presented to neurologists with symptoms that were rated as largely or completely medically unexplained had not improved eight months later. In no case was a disease explanation for the original presenting symptoms subsequently identified.